Bidirectional band-selective magnetization transfer along the protein backbone doubles the information content of solid-state NMR correlation experiments - Jolly, M. M. (J Biomol NMR, 2017)
Resonance assignment is the first stage towards solving the structure of a protein. This is normally achieved by the employment of separate inter and intra residue experiments. By utilising the mixed rotation and rotary recoupling (MIRROR) condition it is possible to double the information content through the efficient bidirectional transfer of magnetization from the CO to its adjacent Cα and the Cα of the subsequent amino acid. We have incorporated this into a 3D experiment, a 3D-MIRROR-NCOCA, where correlations present in the 3D spectrum permit the sequential assignment of the protein backbone from a single experiment as we have demonstrated on a microcrystalline preparation of GB3. Furthermore, the low-power requirements of the MIRROR recoupling sequence facilitate the development of a low-power 3D-NCOCA experiment. This has enabled us to realise significant reductions in acquisition times, allowing the acquisition of a single 3D-NCOCA spectrum suitable for a full backbone resonance assignment of GB3 in less than 24 h. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s10858-017-0147-0) contains supplementary material, which is available to authorized users.